Development and Implementation of the Quality Management System as Applied to the Production of Medical Immunobiological Preparations at the Russian Research Anti-Plague Institute Microbe - O. A. Lobovikova; I. V. Shul'gina; A. K. Nikiforov (Проблемы особо опасных инфекций, 2012)
Developed are the methodical approaches for design and implementation of quality management system(QMS) in the production of preventive and diagnostic medical immunobiological preparations manufactured at the Russian Research Anti-Plague Institute Microbe. Analyzed and generalized is the current legislative-normative framework of Russian Federation in the sphere of quality control and quality assurance. Factors influencing the quality management system are revealed. QMS is certified in conformity with the requirements of international standard ISO 9001.